Design, synthesis, molecular docking, anticancer evaluations, and in silico pharmacokinetic studies of novel 5‐[(4‐chloro/2, 4‐dichloro)benzylidene]thiazolidine‐2, 4‐dione derivatives as VEGFR‐2 inhibitors. Issue 2 (19th October 2020) - El‐Adl, Khaled; El‐Helby, Abdel‐Ghany A.; Sakr, Helmy; Ayyad, Rezk R.; Mahdy, Hazem A.; Nasser, Mohamed; Abulkhair, Hamada S.; El‐Hddad, Sanadelaslam S. A.
Abstract: The anticancer activity of novel thiazolidine‐2, 4‐diones was evaluated against HepG2, HCT‐116, and MCF‐7 cells. MCF‐7 was the most sensitive cell line to the cytotoxicity of the new derivatives. In particular, compounds 18, 12, 17, and 16 were found to be the most potent derivatives over all the tested compounds against the cancer cell lines HepG2, HCT116, and MCF‐7, with IC50 = 9.16 ± 0.9, 8.98 ± 0.7, 5.49 ± 0.5 µM; 9.19 ± 0.5, 8.40 ± 0.7, 6.10 ± 0.4 µM; 10.78 ± 1.2, 8.87 ± 1.5, 7.08 ± 1.6 µM; and 10.87 ± 0.8, 9.05 ± 0.7, 7.32 ± 0.4 µM, respectively. Compounds 18 and 12 have nearly the same activities as sorafenib (IC50 = 9.18 ± 0.6, 5.47 ± 0.3, and 7.26 ± 0.3 µM, respectively), against HepG2 cells, but slightly lower activity against HCT116 cells and slightly higher activity against the MCF‐7 cancer cell line. Also, these compounds displayed lower activities than doxorubicin against HepG2 and HCT‐116 cells but higher activity against MCF‐7 cells (IC50 = 7.94 ± 0.6, 8.07 ± 0.8, and 6.75 ± 0.4 µM, respectively). In contrast, compounds 17 and 16 exhibited lower activities than sorafenib against HepG2 and HCT116 cells, but nearly equipotent activity against the MCF‐7 cancer cell line. Also, these compounds displayed lower activities than doxorubicin against the three cell lines. All the synthesized derivatives 7 –18 were evaluated for their inhibitory activities against VEGFR‐2. The tested compounds displayed high to medium inhibitory activity, with IC50 values ranging from 0.17 ± 0.02 to 0.27 ± 0.03 µM. Compounds 18, 12, 17, and 16 potently inhibited VEGFR‐2 at IC50 values of 0.17 ± 0.02, 0.17 ± 0.02, 0.18 ± 0.02, and 0.18 ± 0.02 µM, respectively, which are nearly more than half of that of the IC50 value for sorafenib (0.10 ± 0.02 µM). Abstract : The anticancer activity of novel thiazolidine‐2, 4‐diones was evaluated against HepG2, HCT‐116, and MCF‐7 cells. Compounds 18, 12, 17, and 16 were found to be the most potent derivatives, with compounds 18 and 12 being nearly as active as sorafenib. All derivatives 7 –18 were also evaluated for their inhibitory activities against VEGFR‐2, with the IC50 values of compounds 18, 12, 17, and 16 being nearly half that of sorafenib.